Improved Speaking Skills In English Language Learning In Elementary Schools - Fransisca, Vika (Publikasi Indonesia, 2023)
English is an important international language used in various areas of life. Therefore, improving the ability to speak English at the elementary school level is a must to face increasingly complex global challenges. Learning English in elementary school is not just about understanding grammatical structures and vocabulary, but also developing effective speaking skills. This study aimed to determine the improvement of speaking skills in English language learning in elementary schools. This research uses a qualitative approach with data collection tools in the form of literature studies. The conclusion is that learners' rejection of the teaching and learning process should be viewed as a